2019
DOI: 10.1017/jlg.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

Macroregional sociolinguistics: Uses and preferences on null direct objects in Spanish

Abstract: This article explores two fundamental dimensions in sociolinguistics: the dynamics of linguistic variation and change in international languages and the exploitation of data proceeding from significant countries. These issues will be addressed through examination of a particular syntactic feature and a possible change in progress: the occurrence of null direct objects in Spanish. It is shown that for Spanish, a widely used international language, social factors have not been decisive in explaining the distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…According to Campos (1986), Spanish null objects are variables bound to a null topic. Although null objects are not regarded as a general characteristic of Spanish, they are allowed to different degrees across the monolingual varieties and the varieties in contact with other languages (e.g., Moreno-Fernández 2019). Relevant to the present study, Moreno-Fernández showed that although null objects are productive in the Andean regions where Spanish is in contact with indigenous languages, their acceptance is low in monolingual varieties, such as the Limeño dialect of Peru which is the focus of this study.…”
Section: Object Expression In Spanishmentioning
confidence: 99%
“…According to Campos (1986), Spanish null objects are variables bound to a null topic. Although null objects are not regarded as a general characteristic of Spanish, they are allowed to different degrees across the monolingual varieties and the varieties in contact with other languages (e.g., Moreno-Fernández 2019). Relevant to the present study, Moreno-Fernández showed that although null objects are productive in the Andean regions where Spanish is in contact with indigenous languages, their acceptance is low in monolingual varieties, such as the Limeño dialect of Peru which is the focus of this study.…”
Section: Object Expression In Spanishmentioning
confidence: 99%
“…Los análisis lingüísticos de PRESEEA tienen en el contraste de usos de variedades diferentes una de sus principales características. Son habituales, pues, las comparaciones de datos de diversa procedencia dialectal o sociolectal (Tagliamonte 2013;Moreno Fernández 2019). Las variables geográficas, sociales y situacionales son exploradas como posibles variables explicativas de los fenómenos analizados, en un intento de obtener el máximo aprovechamiento de los materiales del corpus general.…”
Section: Pautas Metodológicas Para Los Grupos Preseeaunclassified